Silos, politics, and turf wars : a leadership fable about destroying the barriers that turn colleagues into competitors - Lencioni, Patrick, 1965- (San Francisco, CA : Jossey-Bass, 2006)
In this book, the author addresses the costly and maddening issue of silos, the barriers that create organizational politics. Silos devastate organizations, kill productivity, push good people out the door, and jeopardize the achievement of corporate goals. As with his other books, this is a fictional story. It is about Jude Cousins, an eager young management consultant struggling to launch his practice by solving one of the more universal and frustrating problems faced by his clients. Through trial and error, he develops a simple yet ground-breaking approach for helping them transform confusion and infighting into clarity and alignment.
Introduction -- The fable. Part 1. Entrepreneurial ambition -- Part 2. Roller coaster -- Part 3. Rally -- Part 4. Moments of truth -- The theory. Introduction to silos -- Components of the model -- Identifying a thematic goal -- Case studies -- Managing and organizing around the thematic goal -- Thematic goals and long-term context -- Making matrix organizations work -- Getting started -- Acknowledgments -- About the author.
Keywords: Leadership; Organizational behavior